Branching Lithophyllum Coralline Algae: Dominant Reef Builders on Herbivory-Depressed Tropical Reefs after High Coral Mortality - Tom Schils (Diversity, 2023)
A unique shift in benthic community composition, where scleractinian corals are replaced by coralline algae, has been observed on coral reefs in Guam in the western Pacific. Guam’s reefs have been subjected to intense fishing pressure and impaired water quality for decades. Since 2013, heat stress has emerged as an additional major threat to the island’s coral reefs. After a severe coral bleaching and mortality event in 2017, branching coralline algae of the genus Lithophyllum rapidly overgrew dead coral skeletons of the ecosystem engineer Acropora abrotanoides and have since become major components of forereef communities over a broad depth range. By now, the persistence of increased Lithophyllum cover meets the temporal criterium of phase shifts, but accurate estimates on the degree of dominance over appropriate spatial scales are lacking due to the absence of reliable baseline data. The ecological impacts of coral reef transitions towards increased coralline cover are unclear. Whereas carbonate budgets and reef growth could remain positive in the long term, the downstream effect of changes in structural complexity, (micro)habitat diversity, and benthic community composition on ecological processes and reef-associated faunal assemblages is unknown.